The effect of hemodialysis adequacy on ventricular repolarization in end-stage kidney disease - Belma Kalaycı; Engin Onan; Saime Paydaş; Bülent Kaya; Ülkü Adam; Serkan Besli; Süleyman Kalaycı; Fürüzan Köktürk (KARE Publishing, 2019)
Objective: Ventricular repolarization (VR) markers may predict ventricular arrhythmias and cardiac arrest. The aim of this study was to investigate the acute effects of a hemodialysis (HD) session and HD adequacy on VR markers in HD patients. Methods: This cross-sectional study was conducted at 2 university hospitals with 83 patients and VR markers were measured before and after an HD session: QT, QTc, QT minimum, QT maximum, dispersion of QT (QTd), T-peak to T-end (Tp-e) interval, and Tp-e/QT. Kt/V measurements calculated using the second generation Daugirdas formula were used to indicate dialysis adequacy. The patients were divided into 2 groups according to the Kt/V value. Group 1 patients had a Kt/V of ≤1.6 with a standard dialysis dose, and Group 2 comprised those with a measurement of >1.6 with a high dialysis dose. Results: There were 36 patients in Group 1 and 47 patients in Group 2. There were statistically significantly more female patients in Group 2 (p=0.016). After an HD session, heart rate increased, blood pressure decreased, and the QT, QTc, QT maximum, QTd, Tp-e interval, and Tp-e/QT were prolonged (p<0.05). The VR markers measured were similar in the 2 groups. VR markers were not significantly different in diabetic patients. Conclusion: HD may be a risk factor for cardiac arrest because of prolonged VR parameters, independent of HD adequacy. A high dialysis dose may not always be best for the heart.